2016
DOI: 10.5194/tc-10-1571-2016
|View full text |Cite
|
Sign up to set email alerts
|

Snowpack modelling in the Pyrenees driven by kilometric-resolution meteorological forecasts

Abstract: Abstract. Distributed snowpack simulations in the French and Spanish Pyrenees are carried out using the detailed snowpack model Crocus driven by the numerical weather prediction system AROME at 2.5 km grid spacing, during four consecutive winters from 2010 to 2014. The aim of this study is to assess the benefits of a kilometric-resolution atmospheric forcing to a snowpack model for describing the spatial variability of the seasonal snow cover over a mountain range. The evaluation is performed by comparisons to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
85
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 50 publications
8
85
0
3
Order By: Relevance
“…A strong negative bias for SAFRAN 325 can be noticed in the South-Western massifs of the Spanish Pyrenees (Fig. 6g), highlighting a poor representation of the orographic blocking as already noticed in Quéno et al (2016).…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…A strong negative bias for SAFRAN 325 can be noticed in the South-Western massifs of the Spanish Pyrenees (Fig. 6g), highlighting a poor representation of the orographic blocking as already noticed in Quéno et al (2016).…”
mentioning
confidence: 96%
“…On the contrary, the use of SAFRAN irradiances was found to decrease the positive bias obtained with AROME-Crocus. Vionnet et al (2016) and Quéno et al (2016) already showed an overestimation of snow depth by AROME-Crocus in the French Alps and the Pyrenees respec-…”
Section: Sensitivity Of Snowpack Simulations To the Radiative Forcingmentioning
confidence: 99%
See 3 more Smart Citations